Characterization and properties of polyethersulfone/ modified cellulose nanocrystals nanocomposite membranes. (July 2019) - Jonoobi, Mehdi; Ashori, Alireza; Siracusa, Valentina
Abstract: The aim of this study was to develop a novel nanocomposite membranes based on polyethersulfone (PES) and modified cellulose nanocrystals (CNCs) for removal of impurities from wastewater of licorice processing. The surface modification of CNCs was conducted by using (3-aminopropyl) triethoxysilane (APTES) to produce nanocomposite membrane with high efficiency. The chemical modification of CNCs was confirmed by Fourier transform infrared spectroscopy (FT-IR), energy dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), and contact angle measurement. Later on, the mixed matrix nanocomposite membranes were prepared using polyethersulfone (PES) and various contents of modified CNCs (MCNC) (0.1, 0.5, and 1 wt%) as nanoparticles additives. The results showed that the nanocomposite membranes at 1 wt% MCNC concentration had the best efficiency of color removal (94%) and the chemical oxygen demand (COD) reduction (88%) from industrial waste water. The outcomes of this study demonstrated that the silylation of CNC can improve the efficacy of nanocomposite membranes to remove the water impurities, which may be suggested as simple technique for water filtration. Highlights: Cellulose nanocrystals were modified with aminopropyltriethoxysilane. PES-based membranes were prepared using modified cellulose nanocrystals. The prepared nanocomposite membranes were used for pretreatment of wastewater from licorice processing.